1993
DOI: 10.1007/bf01839236
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum C-reactive protein levels in dogs with various disorders and surgical traumas

Abstract: The serum levels of C-reactive protein (CRP) produced as an inflammatory response in dogs with various disorders and surgical traumas were measured by enzyme-linked immunoabsorbent assay and slide reversed passive latex agglutination test (RPLA). The CRP levels were greatly increased 1-2 days after surgery in most of the dogs (n = 29) subjected to surgery. These levels had markedly decreased by the time the sutures were removed. In dogs with various disorders (n = 58), the serum CRP levels at first diagnosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
142
0
5

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(157 citation statements)
references
References 16 publications
10
142
0
5
Order By: Relevance
“…Macroscopically, it seems that the surgical procedure for spinal decompression is much more traumatic than an ovariohysterectomy and that this should be reflected by higher CRP concentrations. CRP values were found to increase much more in orthopaedic surgery compared with ovariohysterectomy in 1 study, and the authors concluded that the rise in CRP was indeed proportional to the intensity of surgical trauma 29 . Another, larger study found the opposite, with the median CRP concentration 24 hours postoperatively being higher in dogs undergoing ovariohysterectomy than in dogs undergoing orthopaedic procedures 9 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Macroscopically, it seems that the surgical procedure for spinal decompression is much more traumatic than an ovariohysterectomy and that this should be reflected by higher CRP concentrations. CRP values were found to increase much more in orthopaedic surgery compared with ovariohysterectomy in 1 study, and the authors concluded that the rise in CRP was indeed proportional to the intensity of surgical trauma 29 . Another, larger study found the opposite, with the median CRP concentration 24 hours postoperatively being higher in dogs undergoing ovariohysterectomy than in dogs undergoing orthopaedic procedures 9 .…”
Section: Discussionmentioning
confidence: 95%
“…These proteins are integral to the acute phase response, which is the body's rapid initial systemic inflammatory reaction to any non-specific tissue injury 10,13,24,29 . Examples of other acute phase proteins are fibrinogen, serum amyloid A, haptoglobin and ceruloplasmin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood CRP concentration is increased in various inflammatory diseases [9,30,16], and its increased level is correlated with the severity and course of the diseases [9,29]. Although few reports are available on blood HMGB1 levels in diseased dogs [13,32], Yu et al recently reported increased plasma HMGB1 levels in dogs with systemic inflammatory response syndrome (SIRS) [32].…”
mentioning
confidence: 99%
“…CRP is a major APP in dogs and its serum concentration can increase rapidly from <1mg/L to >100 mg/L in a number of conditions including surgical trauma, rheumatoid arthritis, polyarthritis, intestinal obstruction, inflammatory bowel disease, lymphoma, acute pancreatitis, pyometra, pneumonia, bacterial enteritis, turpentine oil injection, E.coli endotoxemia, babesiosis, leishmaniosis, leptospirosis, parvovirus infection, trypanosomiasis, Bordetella bronchiseptica and B.canis and Ehrlichia canis infection, bacterial and hemorrhagic enteritis and tumors Jergens et al, 2003and Tecles et al, 2005, Yamamoto, et al, 1993. CRP levels increase from mid-gestation in pregnant bitches, coinciding with embryonic implantation (Eckersall et al, 1993;Vannucchi et al, 2002).…”
Section: Acute Phase Proteins In Canine Medicinementioning
confidence: 99%